2014
DOI: 10.1007/s00404-014-3515-y
|View full text |Cite
|
Sign up to set email alerts
|

C3F gene mutation is involved in the susceptibility to pre-eclampsia

Abstract: The gene polymorphism of complement component C3 was significantly associated with the onset of pre-eclampsia. These results should be confirmed by other studies looking at larger scale to consider this gene as a new biomarker with predictive potential therapeutic consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…C3F has been described as predisposing to PE (55), but we did not find any association of C3F with severe PE. Our result concurs with an early study of C3 allotypes that did not find association of C3F with PE (56).…”
Section: Discussioncontrasting
confidence: 94%
“…C3F has been described as predisposing to PE (55), but we did not find any association of C3F with severe PE. Our result concurs with an early study of C3 allotypes that did not find association of C3F with PE (56).…”
Section: Discussioncontrasting
confidence: 94%
“…Pre-eclampsia is a heterogeneous disease with multiple genetic and environmental risk factors. Although complement activation has been implicated in PE, 33,36,37 the aetiology of an overactive system has not been clearly delineated.…”
Section: Discussionmentioning
confidence: 99%
“…Variant rs2230199 in C3 is known as the slow/fast mutation affecting the mobility of the protein during the electrophoresis process and was associated with the pathogenesis of PE [35]. On the other hand, other published studies found no correlation between this specific variant and preeclampsia [36,37]. Interestingly, according to Banadakoppa et al, the high-risk variant rs800292 in the CFH gene is associated with the activation of the alternative pathway in patients with preeclampsia, only in the coexistence of a variant in the CD46 gene [38].…”
Section: Discussionmentioning
confidence: 99%
“…The patients' group included 30 Caucasian preeclamptic pregnant women with a median age of 36 years [median age (IQR): 36(10,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)] and a median gestational age of 32 weeks. The control group, on the other hand, comprised 15 healthy pregnant women with a median age of 30 years [median age (IQR): 30(11,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) years] and a median gestational age of 30 weeks. Both groups shared similar baseline characteristics, and the control group had otherwise uncomplicated pregnancies.…”
mentioning
confidence: 99%